Changes in Water Quality and Quantity of the Northern Iran’s Wetlands under Land Use Change - Mehrani, Azita; Hamedani, Khosro Shahidi; Hamedani, Dara Shahidi (Journal of Environmental Accounting and Management, 2026)
Wetland modeling under land use change (LUC) plays an important role in the maintenance of these valuable ecosystems. Here, the LUC effect on hydrological changes in Ajigol, Almagol and Alago international wetlands in northern Iran, was investigated using Long-term hydrological impact assessment (L-THIA) model and satellite images (Landsat 5, 7 and 8) during 1987-2018. Correlation test was also performed between LUC parameter and water quality changes during 2003-2018. The results showed that LUCs have directly affected the wetland hydrology in which a correlation coefficient (R-squared) of 0.70, 0.64 and 0.60 was observed between modeled and actual water volume in Almago, Ajigol and Alagol wetlands, respectively. In terms of water quality changes, agricultural land, distance from agricultural lands and urban land changes were closely related to the phosphate, nitrate, acidity, pH and turbidity changes of wetland water over time (P